2014
DOI: 10.1111/j.2047-2927.2014.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of testicular‐internal spermatic vein variation and the recreation of varicocoele in a Sprague‐Dawley rat model

Abstract: SUMMARYMany laboratories tried to recreate the varicocoele model have met with varied success. To recreate a consistent varicocoele model by exploring the anatomic variability of the testicular-spermatic venous system in Sprague-Dawley (SD) rats. Seventy-two sexually mature SD male rats were randomly divided into three groups containing 24 rats per group. Partial ligation of the left renal vein and internal spermatic vein (ISV) communicating branches to common iliac vein and ISV communicating branches ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Infertility in varicocele is due to reduced semen parameters, testicular size and testosterone levels (Miyaoka and Esteves 2012 ; Zhang et al. 2014 ). In this study, we found that sperm count and sperm motility of the vas deferens and epididymis, testosterone levels and left testis weights were significantly reduced in VC + vehicle group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Infertility in varicocele is due to reduced semen parameters, testicular size and testosterone levels (Miyaoka and Esteves 2012 ; Zhang et al. 2014 ). In this study, we found that sperm count and sperm motility of the vas deferens and epididymis, testosterone levels and left testis weights were significantly reduced in VC + vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…Branches of the left renal vein and the left internal spermatic vein (ISV) that communicate with the common iliac vein were partially ligated, and the communicating branches along the left ISV were fully ligated, as described previously (Zhang et al. 2014 ). In brief, the upper left abdominal quadrant was approached, and the left renal and ISV were located through a midline abdominal incision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 first established an ELV model using adult SD rats in 1981, this model has been widely used in different laboratories. 6 8 21 …”
Section: Discussionmentioning
confidence: 99%